2021
DOI: 10.1186/s13063-021-05920-3
|View full text |Cite
|
Sign up to set email alerts
|

SIroliMus coated angioPlasty versus plain balloon angioplasty in the tREatment of dialySis acceSs dysfunctION (IMPRESSION): study protocol for a randomized controlled trial

Abstract: Background Percutaneous transluminal angioplasty is the current standard treatment for arteriovenous fistula (AVF) stenosis. The mid- and long-term patency with plain balloon angioplasty (PBA) is however far from satisfactory. While paclitaxel-coated balloon angioplasty has been shown to be superior to PBA, concern over its safety profile has recently arisen after a reported possible increased mortality risk with a meta-analysis of large lower limb studies. An angioplasty balloon with a new typ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…88,89 Based on the results of these two pilot studies, the IMPRESSION trial comparing DCB angioplasty with MagicTouch AVF SCB versus POBA in dysfunctional AV fistulas was designed. 90 Recently, Tang et al 91 reported the 6 month and 12 month results of the ISABELLA registry, a prospective, single-arm study testing the feasibility and safety of SELUTION SLR SCB in the treatment of failing AV fistulas in 40 patients. 91 Technical and procedural success was 100%, with no adverse events.…”
Section: Sirolimus-coated Balloons In Dysfunctional Arteriovenous Fis...mentioning
confidence: 99%
“…88,89 Based on the results of these two pilot studies, the IMPRESSION trial comparing DCB angioplasty with MagicTouch AVF SCB versus POBA in dysfunctional AV fistulas was designed. 90 Recently, Tang et al 91 reported the 6 month and 12 month results of the ISABELLA registry, a prospective, single-arm study testing the feasibility and safety of SELUTION SLR SCB in the treatment of failing AV fistulas in 40 patients. 91 Technical and procedural success was 100%, with no adverse events.…”
Section: Sirolimus-coated Balloons In Dysfunctional Arteriovenous Fis...mentioning
confidence: 99%
“…The patency rate in our study was also similar to that in previous studies, which ranged from 67% to 82% patency at 3 months. 11,12,16 To improve AVF patency, many devices, including drug-coated balloons, 17 covered stents, 18 and drug-eluting stents, 19 have been developed and published, but more evidence is still needed. In addition, this study also analyzed the risk factors associated with patency and showed that aneurysm size, the use of drugs, and comorbidities were not associated with patency.…”
Section: Acknowledgmentsmentioning
confidence: 99%